Promoting Understandability in Consumer Health Information Search - Yang, Hua (2018)
Search engines have become a common way of obtaining health information. Although access mechanism for factual health in- formation search has developed greatly, complex health searches which do not have a single definitive answer still remain indefinable. Answers to a complex health query contain different viewpoints and confuse a non-expert consumer. It is demanding for a consumer with limited med- ical knowledge background to get a balanced view of the diverse perspectives. This research proposal points out that what consumers need is comprehensive and useful information. To aid consumers get an im- proved understanding of the retrieved contents, the proposed approach is adding additional information to the retrieved contents. One applicable way is classifying the retrieved contents as support, neutral or oppose. The classification labels serve as the extra information to supplement the retrieved contents. Other potential extra information and ways to incorporate the information into a search engine are to be researched into in our later work. In this proposal, the challenges are narrated and related work are reviewed. Research questions and overall goals are stated. The proposed work is discussed and research outline is depicted.